The scorpio races - Stiefvater, Maggie 1981- (Scholastic Press, 2011)
Nineteen-year-old returning champion Sean Kendrick competes against Puck Connolly, the first girl ever to ride in the annual Scorpio Races, both trying to keep hold of their dangerous water horses long enough to make it to the finish line.